Kandungan Nilai Tauhid Uluhiyah Pada Ayat Kursi - Nurhabibi, Nurhabibi; Affifah, Nur (Institut Islam Nahdlatul Ulama Temanggung, 2023)
This article discusses the content of the value of Tawheed of Uluhiyah in the Verse of the Throne with the Comparative Study of the Interpretation of Sayyid Qutb and Ibn Kathir. The article purpose is to find out (1) the values ​​of Tawheed of Uluhiyah contained in the Verse of the Throne (2) The interpretation of Sayyid Qutb and Ibnu Kathir About the value of Tawheed of Uluhiyyah in the Verse of the Throne (3) the implications of Tawheed of Uluhiyah in life. The article uses a qualitative method, sourced from written literature, both the books of Tafsir Fii Zhilal Al-Qur’an, Tafsir Ibn Kathir and other books with a descriptive analysis approach, namely by outlining, analyzing and describing them, also uses the muqaran interpretation method. The results indicate that the methods and styles of interpretation used by Sayyid Qutb and Ibn Kathir are different. The Verse of the Throne, there are values ​​of Tawheed (1) Tawheed of Uluhiyah (2) Tawheed of Rububiyah (3) Tawheed of Asma Wa Sifat. In this study, the discussion of Tawheed is limited to the Tawheed of Uluhiyah, means acknowledging that Allah is the only God Worthy of Worship. So, a Muslim should leave himself and his affairs only to Allah.